Clinico-radiological outcomes of proximal humerus fractures using locking compression plates among adults in a tertiary care hospital: an observational study - V. S. V., Kumar; S., Velmurugan; Kumar, Rajesh; A. S., Hemapriya (International Journal of Research in Orthopaedics, 2024)
Background: Proximal humerus fractures represent 45% of humerus fractures and are the third most common fracture in the elderly due to trivial falls and weakened cancellous bone, and in the young population due to high-energy trauma. These fractures can be disabling and require surgical expertise for a good functional outcome. This study analyzes the clinico-radiological and functional outcomes of adult patients with proximal humerus fractures treated with locking compression plates. Methods: A prospective observational study was conducted on patients with proximal humerus fractures treated with locking compression plates from June 2022 to June 2023 at SIMS Hospital, Chennai. Functional outcomes were measured using the SPADI score and radiological union of fractures at follow-ups of 2, 6, 12, and 24 weeks. Results: In this study, 34 patients underwent ORIF with locking compression plates. All fractures healed completely without secondary procedures, nonunion, malunion, or implant failure. No postoperative complications were observed. The average time for radiological union was 14.5±2.4 weeks. The SPADI scores at 2, 6, 12, and 24 weeks were 82, 63.26, 22.26, and 4.06, respectively, showing statistically significant improvement (p < 0.05). Conclusions: ORIF with locking compression plates, combined with proper anatomical reduction and suture augmentation of the rotator cuff, yields early ROM return and good functional outcomes. This method achieves earlier radiological union compared to other methods, making it the preferred choice for proximal humerus fractures across all age groups.